Meningkatkan Hasil Belajar Peserta Didik Pada Materi Aku Memiliki Kemampuan Dan Kemampuanku Terbatas Melalui Model Pembelajaran Problem Based Learning Di SMP Negeri 3 Belimbing Kabupaten Melawi - Margareta Margareta (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve student learning outcomes on the topic "I Have Abilities and My Abilities Are Limited" at SMP Negeri 3 Belimbing through the Problem-Based Learning (PBL) model. The focus of the research is on seventh-grade students, where some students showed low learning outcomes. The study was conducted in two cycles; in Cycle I, without PBL, the results were unsatisfactory. However, in Cycle II, the implementation of PBL showed significant improvements in scores and learning completeness, with results exceeding the Minimum Completeness Criteria (KKM) of 75.